The sorghum shoot fly, Atherigona soccata rondani (diptera: muscidae) attacking some gramineous forage crops in Egypt - El-Serwy, S. A. (2006)
The sorghum shoot fly, Atherigona soccata Rondani, attacks sorhgum ratoon (Sorghum bicolor (L.) Moench) at Sids and AI-Aiat with Atherigona humeralis (Wiedemann) on Sudan grass (Sorghum vulgare var. sudanense Hitch.) and Atherigona bedfordi Emden (new record) on Barnyard grass (Echinochloa crus-galli (L.) P. Beauv) at AI-Aiat in Middle Egypt. The shoot flies were generally active during the year and passing from crop to crop. It infested ratoon of sorghum plants left in the field after harvest reaching about 12% at Sids in 2002.
Includes references.
Summary in Arabic.
1
Keywords: Sorghum shoot fly -- Control; Diptera -- Biological control; Muscidae; Forage -- Yields; Forage plants -- Diseases and pests -- Egypt; Sorghum -- Yields; Biological pest control agents; Sorghum -- Diseases and pests -- Egypt